Virus-vector relationships of chickpea chlorotic dwarf virus (CpCDV) and sesame jassid (Orosius orientalis) in chickpea - Hamed, Abdelmagid; Dafalla, Gassim (Gezira Journal of Agricultural Science, 2011)
Serological testing using tissue blot immunoassay (TBIA) showed a close association between CpCDV and stunt disease in chickpea. Therefore, a glasshouse investigation was initiated at Hudeiba Research Station, the River Nile State, Sudan, in 2006 to verify the role of O. orientalis as an insect vector in disease transmission. The results showed that disease transmission efficiency was increased as the number of leafhopper ( O. orientalis ) increased from one to 15 insects/ plant. The minimum virus acquisition and inoculation access periods (AAP and IAP) were found to be about 5 min. The latent and retention periods were 180 min and 17 days, respectively.     أوضح استعمال اختبار الوصمة النسيجية السيرولوجى العلاقة الوطيدة بين فيروس تقزم واصفرار الحمص و مرض التقزم. تم اجراء عدد من التجارب بالبيت الزجاجى بمحطة بحوث الحديبة بولاية نهر النيل في عام  2006 وذلك لمعرفة دور حشرة نطاط الاوراق Orius orientalis فى نقل المرض.  أوضحت النتائج ان فاعلية الحشرة فى نقل المرض ازدادت مع زيادة عدد الحشرات المستعملة من واحد الى 15 حشرة، و كذلك أوضحت النتائج أن أقل فترة لاكتساب ونقل الفيروس بواسطة الحشرة هى حوالى 5 دقائق و فترة حضانة الفيروس حوالى 3 ساعات. وجد كذلك ان للحشرة القدرة للاحتفاظ بالفيروس لمدة 17 يوماً وحتى موتها.